PENEGAKAN HUKUM TINDAK PIDANA PEMBUANGAN LIMBAH KAPAL BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLIDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DI WILAYAH HUKUM KEPOLISIAN RESOR SIAK - Feri Feri; Zulfikar Jaya Kusuma; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
One of the environmental pollution is water pollution through rivers, and one of the factors is wastedisposal by ships on the Siak River. The level of pollution of the Siak River, is increasingly worrisome. TheSiak River has been proven to be polluted but the Environmental Criminal Law Enforcement on the SiakRiver has not run optimally. The police in terms of enforcement is still slow, because law enforcementofficers carry out their duties if there are reports from the media. Meanwhile in Indonesia there is anindependent supervisory institution whose function is to supervise and the institution is the Office of theEnvironment of Siak Regency and the Police of Siak Resort. The purpose of this thesis, namely First to findout the law enforcement of criminal acts of ship waste disposal in the jurisdiction of the Police of SiakResort. Secondly to find out the obstacles in law enforcement of criminal acts of ship waste in thejurisdiction of the Siak Resort Police. Third, to find out the efforts made to overcome the legal barriers tocriminal acts of vessel waste disposal in the jurisdiction of the Siak Resort Police.This type of research can be classified in the type of sociological research. The research locationsare the Siak Regency Environmental Office and the Siak Resort Police. The data sources used are primarydata and secondary data. Data collection techniques are interviews, questionnaires and literature review.After the data collected is then analyzed qualitatively by using the deductive method, namely drawingconclusions from things that are general to things that are specific.From the results of the study there are three main things that can be concluded. First, theenforcement of environmental criminal law by the Environmental Service (DLH) and the Siak Resort Policetowards perpetrators of environmental destruction and pollution is carried out in a pre-emtive, preventiveand repressive manner. The two problems faced by the TIPITER Unit of the Siak Resort Police are in theenforcement of environmental criminal law where internal and external constraints have been found. Thethree efforts made by the TIPITER Unit of the Siak Resort Police and the Siak Regency EnvironmentalAgency (DLH) are supposed to overcome obstacles both internally and externally.Keywords: Environmental Pollution - Law Enforcement - Siak River